2007
DOI: 10.1007/s11146-007-9032-z
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Railway Stations on Residential and Commercial Property Value: A Meta-analysis

Abstract: Railway stations function as nodes in transport networks and places in an urban environment. They have accessibility and environmental impacts, which contribute to property value. The literature on the effects of railway stations on property value is mixed in its finding in respect to the impact magnitude and direction, ranging from a negative to an insignificant or a positive impact. This paper attempts to explain the variation in the findings by meta-analytical procedures. Generally the variations are attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 498 publications
(162 citation statements)
references
References 26 publications
5
133
0
3
Order By: Relevance
“…A recent study by Debrezion et al (2007) also reported positive increments in commercial property values closer to railway stations in the Netherlands. ey also found that railway stations are expected to have a higher positive effect on commercial properties compared to residential properties for relatively short distances from the stations.…”
Section: Proximitymentioning
confidence: 80%
“…A recent study by Debrezion et al (2007) also reported positive increments in commercial property values closer to railway stations in the Netherlands. ey also found that railway stations are expected to have a higher positive effect on commercial properties compared to residential properties for relatively short distances from the stations.…”
Section: Proximitymentioning
confidence: 80%
“…Demographic and spatial LU impacts of TINs, measured by changes in population and employment density, land cover and development type (residential, office, commercial, industrial) are reviewed, whereas economic outcomes measured by economic performance indicators such as the Gross Domestic Product (GDP) and property values are excluded (examined elsewhere by authors such as Banister & Berechman, 2001;Debrezion, Pels, & Rietveld, 2007). The focus on empirical findings means that ex-ante studies on landuse-transport modelling (LUT) are outside the scope of this paper (for an overview, see Iacono, Levinson, & El-Geneidy, 2008;Wegener, 2004).…”
Section: Scopementioning
confidence: 99%
“…The total aggregated score obtained for each sub-criterion was then normalized into a dimensionless effect score between 0 and 1. This is a usual choice for the domain of vulnerability assessment in disaster studies (Cutter et al 2009). …”
Section: Criteria Rankingmentioning
confidence: 99%